Isolation of a Polygalacturonase-Inhibiting Protein (PGIP) from Wheat - Kemp, Gabré; Bergmann, Carl W.; Clay, Ron; Van der Westhuizen, Amie J.; Pretorius, Zacharias A. (Molecular plant-microbe interactions, 2003)
Evidence for the presence of a polygalacturonase-inhibiting protein (PGIP) from a monocotyledonous cereal is presented. A 40.3-kDa PGIP that was closely associated with the cell wall was acetone-extracted and purified from wheat (Triticum aestivum L.) leaves and stems. Wheat PGIP exhibited a highly selective inhibitory activity against endopolygalacturonase (EPG) from various fungi. Of nine EPG tested, wheat PGIP only inhibited EPG from Cochliobolus sativus, a pathogen of the tribe Poaceae. A short N-terminal amino acid sequence of wheat PGIP shows no similarity to any other characterized PGIP.